Hubungan Antara Lama Paparan dengan Kapasitas Paru Tenaga Kerja Industri Mebel di CV. Sinar Mandiri Kota Bitung - Kumendong, Donald J. W. M.; Rattu, Joy A.M; Kawatu, Paul A.T. (KESMAS, 2012)
The human lungs as an instrument of pulmonary ventilation in respiratory system in the human body’s. lungs function may decrease due to strikes in the process of physiological mechanisms, one of which is caused by exposure to dust. The continuosly dust exposure can cause problems in the lungs, it also cause chronic lung disease. The aim of research was know the relationship between the long duration of the exposure and lung capacity of workers in the furniture industry at CV. Sinar Mandiri Bitung City. This research was an analytic survey, with a cross-sectional approach. Sample of study was the workers of production, which amounts of 30 respondents and it was a population total study. The data were collected by interviews to know the characteristics of respondents and the measurement of workers lung capacity by using spirometer (peak flow meter). Data was analyzed with Fisher’s Exact Test and using program SPSS version 17.0.The result showed that of 30 respondents who have been checked there are 30 percets who have abnormal FEV1 values or the category of disability. According to the results of statistical test, the probability value was 1,000 (p>0,05).That there was no significant relationship between the long duration of exposure and lung capacity of workers. Recommendation to the chief of company, there was needed monitoring of workers physical condition and working environment. There also needed a prevention way by using mask, as well as needed a supervision and guidance to the companies about occupational health and safety by related department. ABSTRAKParu-paru sebagai alat ventilasi dalam sistem pernafasan bagi tubuh, fungsi kerja paru dapat menurun akibat adanya gangguan pada proses mekanisme faal yang salah satunya disebabkan oleh pemaparan debu. Pemaparan debu yang secara terus-menerus selain dapat menimbulkan gangguan fungsi paru juga dapat menyebabkan terjadinya penyakit paru kronik. Penelitian ini bertujuan untuk mengetahui hubungan antara lama paparan dengan kapasitas paru pekerja industri mebel di CV. Sinar Mandiri Kota Bitung.Penelitian ini merupakan penelitian yang bersifat survei analitik, dengan pendekatan cross sectional. Sampel penelitian adalah pekerja di bagian produksi yang berjumlah 30 orang dan merupakan studi total populasi. Pengumpulan data dilakukan dengan wawancara untuk mengetahui karakteristik responden dan pengukuran kapasitas paru pekerja dengan alat spirometer. Analisis data dilakukan dengan Fisher’s Exact Test dan menggunakan bantuan SPSS versi 17.0. Hasil penelitian menunjukkan bahwa dari 30 responden yang diperiksa terdapat 30% yang mempunyai nilai FEV1 tidak normal atau dikategorikan mengalami gangguan. Berdasarkan hasil uji statistik, nilai probabilitas sebesar 1,000 (p > 0,05)Tidak terdapat hubungan yang bermakna antara lama paparan dengan kapasitas paru pekerja. Saran untuk pimpinan perusahaan perlu dilakukan pemantauan kondisi fisik pekerja dan lingkungan kerja, perlu dilakukan upaya pencegahan dengan penggunaan masker, serta perlu dilakukan pengawasan dan pembinaan terhadap perusahaan mengenai kesehatan dan keselamatan kerja oleh dinas terkait.